2016
DOI: 10.2527/jas.2016-0807
|View full text |Cite
|
Sign up to set email alerts
|

Effect of ractopamine hydrochloride (Optaflexx) dose and duration on growth performance and carcass characteristics of finishing steers1

Abstract: Three experiments evaluated the effects of ractopamine hydrochloride (RAC) dose and duration on growth performance and carcass characteristics of feedlot steers. In total, 1,509 crossbred steers (530 kg initial BW [SD 22]) were used in a randomized complete block design using a 3 × 3 factorial treatment structure. Treatments consisted of RAC dose (0, 100, or 200 mg/steer daily) and duration (28, 35, or 42 d) of RAC feeding prior to harvest. Initiation of RAC dose was staggered (7 d apart) based on RAC duration… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…Often monensin and tylosin are provided concurrently to cattle in North American feedlots. The active ingredient in Optaflexx is ractopamine-HCl and has been found to improve average daily gain, feed efficiency, and carcass gain 34 , 35 . However, there is no available information that could link Optaflexx administration and the microbial pattern in the gut.…”
Section: Discussionmentioning
confidence: 99%
“…Often monensin and tylosin are provided concurrently to cattle in North American feedlots. The active ingredient in Optaflexx is ractopamine-HCl and has been found to improve average daily gain, feed efficiency, and carcass gain 34 , 35 . However, there is no available information that could link Optaflexx administration and the microbial pattern in the gut.…”
Section: Discussionmentioning
confidence: 99%
“…Often monensin and tylosin are provided concurrently to cattle in North American feedlots. The active ingredient in Optaflexx is ractopamine-HCl and has been found to improve average daily gain, feed efficiency, and carcass gain 33,34 . However, there is no available information that could link Optaflexx administration and the microbial pattern in the gut.…”
Section: Discussionmentioning
confidence: 99%
“…No difference in 12th rib backfat, KPH, YG, or marbling score was observed in this study due to supplementation of Zn, RH, or their interaction (Table 4-1; P ≥ 0.17). Several studies have observed lesser fat thickness and KPH along with lower marbling scores and YG in carcasses from cattle supplemented with RH Bittner et al, 2016;Trotta et al, 2019).…”
Section: Carcass Characteristics and Proximate Analysismentioning
confidence: 98%
“…The use of RH to improve growth performance and carcass lean yield has been extensively studied Bittner et al, 2016Bittner et al, , 2017. However, many results related to these characteristics are inconsistent.…”
Section: Carcass Characteristics and Proximate Analysismentioning
confidence: 99%